Apical transportation with different root canal preparation techniques using edgEEvolve rotary instruments - Seyyed Mohsen Hasheminia; Ali Nohekhan; Saber Khazaei; Alireza Farhad (Wolters Kluwer Medknow Publications, 2022)
Background: This study aimed to investigate the extent of apical transportation following instrumentation with EdgeEvolve rotary instruments applying single-length and crown-down techniques. Materials and Methods: In this experimental in-vitro study, 60 mandibular molars with mesiobuccal curvatures of 20°-40° were selected, and digital radiographic images were taken. Teeth were randomly assigned into two groups of single-length and crown-down preparation techniques. In both mentioned groups, EdgeEvolve rotary system was used. After preparation, the same as the previous ones, digital radiographic images were taken from the canals. The data were analyzed using Student's t-test and ShapiroWilk normality test (P = 0.05). Results: The mean standard deviation (SD) for apical transportation in the single-length and the crown-down group was 4.42 (2.9) and 7.48 (3.9) degrees, respectively (P < 0.05). The mean SD of the preparation time in the single-length and crown-down group was 135.07 (30.8) and 109.07 (20.8), respectively (P < 0.05). The apical transportation and the time of preparation between the two groups were significant. Conclusion: Using EdgeEvolve rotary instruments canal preparation with both single-length and crown-down techniques led to some degrees of apical transportation.